Draft Annual Plan (1970-71) Part-I Union Territory of Pondicherry - Planning Commission (Planning Commission, 1970)
The Union territory of Pondicherry comprises the four regions of Pondicherry, Karaikal , Mahe and Yanam, covering an area of about 479.2 sq. kms. with a population of 3.69 lakhs, according to the 1961 census. The Pondicherry region (area 290.1 sq. kms.) is on the east-coast, about 160 kms. south of Madras. Pondicherry region is not a contiguous area but is inter-spersed with enclaves of Tamil Nadu. It consists of 267 villages, with a total population of 2.59 lakhs. About 160 kms. further south on the east coast lies the Karaikal region (area 158.sq.kms.) consisting of 118 villages with a population of 84,000.
Government of Pondicherry Finance Planning and Local Administration Department